2001
DOI: 10.1007/s004210100416
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular contractile performance in the early stage of hypertension in humans

Abstract: The aim of the present study was to assess how cardiac structural changes contribute to increasing left ventricular pump function during exercise in subjects with mild hypertension. In 23 young male subjects with mild hypertension and 12 male normotensive control subjects, left ventricular function was measured echocardiographically using the fractional shortening/ meridional stress relationship at rest and during longlasting exercise at the anaerobic threshold. Mean exercise duration and intensity were 61 (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies demonstrated sex differences in the cardiovascular response during cycle exercise (17,35). 3) Use of two-dimensional ultrasound to quantify ventricular volumes has its limitations; however, it has previously been used for volume measurement during submaximal and maximal exercise in numerous populations (16,36,41). Because this technique was applied across all groups, any errors were systematic in nature.…”
Section: Ventricular-vascular Coupling and V O 2 In Htrmentioning
confidence: 98%
“…Previous studies demonstrated sex differences in the cardiovascular response during cycle exercise (17,35). 3) Use of two-dimensional ultrasound to quantify ventricular volumes has its limitations; however, it has previously been used for volume measurement during submaximal and maximal exercise in numerous populations (16,36,41). Because this technique was applied across all groups, any errors were systematic in nature.…”
Section: Ventricular-vascular Coupling and V O 2 In Htrmentioning
confidence: 98%
“…Although LV ejection performance can be adequately increased by wall thickening in early hypertrophy the actual LV contractility is already depressed (Palatini et al 2001). Due to the lack of human myocardial tissue at this early stage of hypertrophy, physiological data on the myocyte level are rarely available.…”
Section: Post-rest Potentiation Of Contractionmentioning
confidence: 98%
“…Peak V _O 2 is related to peak cardiac output (Di Bello et al 1996;Schulman et al 1996). In a group of mildly hypertensive and normotensive subjects, stress-corrected MWS was lower in hypertensive than in normotensive subjects both at baseline and during exercise despite an approximately similar peak V_O 2 reached by the two groups (Palatini et al 2001). …”
Section: Discussionmentioning
confidence: 96%